Stereotactic Body Radiation Adoption Impacts Prostate Cancer Treatment Patterns - Stencel, Michael G.; Wu, Shan; Danielle, Sharbaugh R.; Yabes, Jonathan G.; Davies, Benjamin J.; Sabik, Lindsay M.; Jacobs, Bruce L. (Urology (Ridgewood, N.J.), 2024)
To investigate stereotactic body radiation (SBRT) adoption for prostate cancer. As evidence supporting SBRT mounts, its utilization and impact relative to other prostate cancer treatments is unknown. We used SEER-Medicare to identify patients diagnosed with localized prostate cancer from 2008 to 2017. We then identified physician networks by identifying the primary treating physician of each patient based on primary treatment, then linking each physician to a practice. We examined trends in prostate cancer treatment between networks performing SBRT or not using chi-squared tests and logistic regression models. There were 35,972 patients who received treatment for prostate cancer at 234 physician networks. Of these patients, 30,635 were treated in a non-SBRT network (n = 190), while 5337 received treatment in a SBRT network (n = 44). Patients who received care in an SBRT network were more likely to live in metropolitan areas ≥1 million (70% vs 46%, P <.001), have a higher median income >$60,000 (62% vs 42%, P <.001), and live in the northeast (35% vs 12%) or west (40% vs 38%, P <.001) compared to non-SBRT networks. In SBRT networks, more patients received IMRT (31% vs 23%), and fewer patients received prostatectomy (16% vs 23%) or active surveillance (15% vs 19%) compared to non-SBRT networks. Black men were 45% less likely to receive SBRT (OR=0.55, CI: 0.36-0.85) compared to White men. SBRT utilization is increasing relative to other prostate cancer treatments. Prostate cancer treatment mix is different in networks that offer SBRT, and SBRT is less available to some patient groups, raising concern for novel treatment inequity.